الاعتراف في العمل ودوره في تثمين الموارد البشرية - هيشر, سميرة (Recherches économiques et managériales, 2013)
لقد آن الأوان لإدارة المؤسسة أن تولي اهتماما أكبر لمواردها البشرية بصورة مستمرة، والابتعاد عن تذكرهم فقط عندما تحتاجهم وتنسى جهودهم عند حصاد النتائج ونسب النجاح لنفسها، لذلك بات من الضروري أن تعمل على جعل مواردها البشرية تشعر بأهميتها في إحراز النجاح والتقدم للمؤسسة، وهذا الهدف لا يتحقق إلا من خلال خطوة يمكن للمؤسسة أن تقوم بها ألا وهي عملية تثمين مواردها البشرية، هذه العملية تتم من خلال عدد من الأساليب من أهمها الاعتراف الذي يعد عنصر أساسي في وسط العمل فبدونه يكون هناك فجوة في العلاقات الإنسانية بين أفراد المؤسسة، كما أنه وسيلة لجعل أماكن العمل أكثر إنسانية لتحفيز الموارد البشرية، وسنبرز من خلال هذه الورقة البحثية كيفية مساهمة الاعتراف في العمل في تثمين الموارد البشرية، بالإضافة إلى معرفة ماهي أهم الآثار الناتجة عن عملية تثمين الموارد البشرية. الكلمات المفتاحية: الموارد البشرية، تثمين الموارد البشرية، الاعتراف. Abstract :    It is high time for the management of the institution to pay more attention to its human resources at all times , and to stray of  reminding them only when they need them and forgetting  their efforts when it came’s to extracting  results and  considering success to be their only, thence it becomes necessary to work on making their human resources, feel their importance in achieving success and the s’advance, this can be achieved thigh a process of valuing its human resources, This operation is carried out following different methods which  "recognition" represents its most important one, recognition is a very  essential element in the field of the working without  which  a serious gap will be found in  at the level of human relations  and between the  members of the institution,,  It is also a way to make the working places more humanistic to motivate  human resources, in our study, an effort is made to discern how the method  recognition in the working places , can contribute in valuing human resources,  it also attempted to pinpoint to the most important effects of the process of valuing human resources. Keywords : human resources, valuing human resources, the recognition.